GAMBARAN PERILAKU IBU DALAM PENCEGAHAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS SANDI KABUPATEN WAKATOBI - Jafriadin; jumadi; waode Azfari Azis; La Ode Muh Taufiq (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2022)
Occurrence diarrhea in toddlers cannot be separated from role behavioral factors that maternal behavioral interactions. Data from Sandi Health Center in 2020 showed that of 314 toddlers there were of 65 toddlers who experienced diarrhea. Purpose study was to find out the description of mother's behavior in form exclusive breastfeeding, hand washing habits, use clean water, selection children's playgrounds, and management children's feces in preventing diarrheal diseases in toddlers. Type of research used is descriptive observational. Population and sample in this study were 60 families, sample amounting to 60 families and side method used was total sampling. Research data collection consisted primary data obtained by questionnaire and secondary data obtained from report notes Sandi Health Center. Data processing is done computerized using SPSS program. Analysis used is univariate analysis, namely to see appearance frequency distribution each variable studied. Data was analysis by univariate approach 78.3% have good behavior in exclusive breastfeeding, there are 83.3% have good behavior in washing hands, there are 100% have good behavior in use of clean water, there are 73.3% have good behavior in selection of children's playgrounds, and there are 68.3% have good behavior in management of children's feces as an effort to prevent diarrhea in toddlers. Conclusion shows that mothers have good behavior in preventing diarrhea in toddlers in Sandi Health Center District Wakatobi Regency. Suggestions in form need for increased education to the community about efforts to prevent diarrhea especially in toddlers.